2015
DOI: 10.1590/1983-40632015v4533791
|View full text |Cite
|
Sign up to set email alerts
|

Fosfito de potássio não protege plantas de milho contra os efeitos fitotóxicos do glyphosate1

Abstract: RESUMOExistem relatos controversos sobre o efeito do fosfito de potássio, associado ou não ao glyphosate, em plantas. Alguns indicam que o fosfito de potássio pode causar injúrias, quando aplicado isoladamente, enquanto outros destacam que ele pode reduzir a injúria causada pelo glyphosate, quando aplicado em conjunto com este herbicida. Este estudo objetivou avaliar o efeito do fosfito de potássio, em associação ou não com o glyphosate, sobre a injúria visual, acúmulo de massa seca, níveis de compostos indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…As in the present study ( Figure 7 ), other authors also observed an increase or little change in the concentration of aromatic amino acids after exposure of plants to different concentrations of glyphosate [ 39 , 56 , 58 , 61 , 62 , 63 , 64 , 65 , 66 ]. A possible explanation for the increase in aromatic amino acids after herbicide application would be a possible regulatory mechanism after EPSPS expression that controls the content and changes in metabolic regulations in the biosynthesis of these amino acids and protein hydrolysis [ 61 , 65 , 66 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…As in the present study ( Figure 7 ), other authors also observed an increase or little change in the concentration of aromatic amino acids after exposure of plants to different concentrations of glyphosate [ 39 , 56 , 58 , 61 , 62 , 63 , 64 , 65 , 66 ]. A possible explanation for the increase in aromatic amino acids after herbicide application would be a possible regulatory mechanism after EPSPS expression that controls the content and changes in metabolic regulations in the biosynthesis of these amino acids and protein hydrolysis [ 61 , 65 , 66 ].…”
Section: Discussionsupporting
confidence: 87%
“…The increase in chemical acid at low doses was also observed in sugarcane [ 21 ], in which the authors characterized this increase as the hormetic effect of glyphosate, where the application of 1.8 g ae ha −1 at 35 DAA presented the highest concentrations. In maize, an increase in quinic acid was observed after application of 72 and 720 g ae ha −1 ; however, higher concentrations were observed at the highest dose [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The glyphosate-tolerant soybean expresses two versions of the EPSPs enzyme, one native to the species and the other introduced from Agrobacterium sp., which is tolerant to the herbicide (Bervald et al, 2010). Thus, there is no accumulation of chiquimate-3-phosphate in the plant and no reduction in biomass or other components of agronomic interest in resistant plants (Gomes et al, 2015). Some authors consider that the symbiotic bacterium does not have the same tolerance to the herbicide, which may reduce its efficiency; however, it is also reported that both the plant and the bacterium have the capacity to recover after a few days of application (King et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds originate from secondary metabolism. The more importante are tannins, lignans, coumarins, lignins and flavonoids (Gomes et al, 2015). Among the various functions of these metabolites, it is worth noting their antimicrobial and antioxidant action, due to the absorption and neutralization of free radicals, chelating the triplet and singlet oxygen or decomposing peroxides (Olivoto et al, 2017).…”
Section: Resultsmentioning
confidence: 99%